Permeable Pavement with Micro-Detention Pond Using Precast Honeycomb Structure (StormPav) : A Green Pavement Practice - Norazlina, Bateni; Rosmina, Ahmad Bustami; Md Abdul, Mannan; Darrien Mah, Yau Seng; Lai, Sai Hin (Malaysian Stormwater Organisation, 2024)
A newly designed system of dual function, a permeable road pavement and a detention pond storage namely STORMPAV is investigated for the effectiveness as green pavement system. The system consists of precast honeycomb sets at top as road surface and at bottom as base plate. In the middle is a cylindrical hollow rain barrel as a detention storage. The laboratory works indicate that the StormPav has met the basic hydrological design considerations, like those in the typical permeable pavement, from the perspective of permeability rates, infiltration capacity, storage and detention capability. The system can provide significant peak runoff reduction, resulting from the depression storage which is able to store the 10 to 100-year major storm events within duration of 20 to 30 minutes without overflow. In other words, such a condition allows the system to cope with the urban major storms which normally have a time of concentration of 10 to 15 minutes. Next, a case study is simulated in Stormwater Management Model (SWMM), to assess the hydrological performance of StormPav and compared it with the conventional road pavement and other types of permeable pavements, such as pervious concrete (PC) and permeable interlocking concrete pavers (PICP). StormPav results in higher runoff reduction, the lowest runoff coefficients, and peak flowrate. It also demonstrates faster time taken to infiltrate to the ground with a higher rate of infiltration loss, in comparison to those recorded for PC and PICP. These results display the effectiveness of StormPav as a permeable pavement with the presence of subsurface micro-detention storage. Hence, it is deduced that StormPav is a good practice to control peak flow at source.